(untitled) (Research, Society and Development, 2023)
Introduction: The management of a Pediatric Intensive Care Unit (PICU) relies on the analysis of the main sector demands and the characterization of admissions. The epidemiological study aims to improve patient prognosis by collecting data that systematize the key events in the units, enabling the development of an effective planning for operation, organization, and adaptation of care. Objective: To describe the epidemiological profile of patients admitted to the Pediatric Intensive Care Unit of the University Hospital of Western Paraná over a one-year period. Methodology: Data collection and analysis of 162 admissions in the year 2021 through electronic medical records. All analyses were performed using XLSTAT® Software Version 2014. Results: Neurological diseases were the most prevalent (50%), followed by respiratory diseases (31.48%); children under 1 year old were statistically more frequent; the length of stay in the unit was predominantly 1 to 2 days; oxygen therapy was used in 77.78% of admissions; 69.13% of admissions required invasive mechanical ventilation; 87.04% did not require tracheostomy; 98.15% of patients received physiotherapy care; 89.51% of patients were discharged from the unit. Final considerations: The traced epidemiological profile obtained similar results to those of other institutions. The importance of primary care in programs aimed at children’s health is highlighted, considering avoidable admissions. The collected data may assist in conducting new relevant epidemiological studies for the training of PICUs and proper treatment of admitted children.